E0272 Low testosterone levels are inversely associated with carotid artery plaque formation. (17th November 2010) - Qiang, Ma; Qingli, Cheng; Jing, Wen
Abstract : Objective: To study the relationship between endogenous sex hormone levels and atherosclerosis of the carotid artery measured by ultrasonography. Methods: Analysis of the healthy elders from a population-based cohort study in 9 communities of Beijing. carotid intima-media thickness (IMT) and atherosclerotic plaques were determined ultrasonographically. Sex hormone levels were measured by immunoassay. The data were analysed with ANOVA and logistic regression analysis. Results: There was a inverse association between testosterone and plaque formation in females (p<0.001), whereas no association was found in males. Logistic regression analysis showed that females with a testosterone level in the lowest quintile (<0.49 nmol/l) were more likely (OR=3.11, p=0.002) to be in the plaque formation independently of age and the other risk factors. Age (OR=1.07 year-1), LDL (OR=1.65, p=0.027), physical exercise (OR=0.54, p=0.006), and IL-6 (OR=1.05, p=0.022) were also independently associated with plaque formation. Conclusions: Testosterone concentrations are negatively associated with carotid artery atherosclerosis in females, experimental and prospective studies are needed to determine the possible therapeutic role of testosterone in atherosclerosis.